PEMBERDAYAAN IBU PKK DESA BULUREJO KECAMATAN BENJENG KABUPATEN GRESIK MELALUI KEGIATAN PENGOLAHAN TANAMAN OBAT KELUARGA (TOGA) - Afkar, Taudlikhul; Setiyowati, Diah; Romadlona, Rahmah Dwi; Jebaru, Agapitus Harimasri (Jurnal Abadimas Adi Buana, 2017)
Medicinal plant is a plant that has many efficacy especially in the health field. because of the efficacy of the medicinal plants in community service activities in the form of training is done processing of medicinal plants by processing ginger (Zingiber officinale) into instant ginger. this training to program at village level to educate women on various aspects of family welfare Bulurejo Benjeng Gresik. the purpose of this activity is to utilize medicinal plants and can improve the health of the community independently by utilizing medicinal plants, as well as provide knowledge to the community of the importance of medicinal plants for health and gives an understanding of how management and utilization of medicinal plants, as well as familiarize the people to plant and utilizing medicinal plants in the home environment, the methods used are active learning and parcipatory learning, which includes lectures, practice of processing plants healthy and continue with the discussion of the results of this training, this training showed knowledge about the importance of medicinal plants for health, as well as skills processing of medicinal plants for program at village level to educate women on various aspects of family welfare. Keywords: Empowerment, Processing, Medical Health